An Appraisal of Muon Neutrino Disappearance at Short Baseline - L. Stanco; S. Dusini; A. Longhin; A. Bertolin; M. Laveder (Advances in High Energy Physics)
Neutrino physics is nowadays receiving more and more attention as a possible source of information for the long-standing problem of new physics beyond the Standard Model. The recent measurement of the third mixing angle